REVIEW JURNAL : FORMULASI KRIM EKSTRAK ETANOL DAUN KELOR (Moringa Oleifera Lamk) - Radisty, Denisha; Dhea Putri Maharani; Armila Nurma (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Moringa oleifera Lamk, the plant that has efficacy as anti-inflammatory agent, is potential to be made as cream preparation. The study aimed to to get the best cream formula containing leaf extract of Moringa oleifera Lamk. The study was conducted by making cream preparations with three different formulas (F1, F2 and F3) containing 10% w/w Moringa leaf extract. Evaluation of cream preparations carried out for 4 weeks of storage included organoleptic tests (color, odor and consistensy), homogeneity, pH, viscosity, washability, cream type, and irritation test. The results showed that all formulas (F1, F2 and F3) met the requirements of good and non-irritating creams. The best cream formula based on 4 weeks storage study was F3 containing Moringa leaf extract 10%, stearic acid 10%, liquid paraffin 2%, cetyl alcohol 2%, span 80 1.5%, tween 80 3.5%, glycerin 7.5%, titanium dioxide 0.7%, oleum rosae 15 drops, nipagin 0.18%, nipasol 0.02%, and aquadest add 50% w/w.